Selaginella qingchengshanensis (sect. Heterostachys; Selaginellaceae), a new species from Sichuan, China - He, Meng; He, Zhao-Rong; Zhang, Li-Bing; Zhou, Xin-Mao (Phytotaxa, 2021)
Based on morphological and phylogenetic studies, Selaginella qingchengshanensis, a new species in S. sect. Heterostachys from Sichuan, China is described and illustrated. Morphologically, the new species is similar to S. amblyphylla, but has sterile leaves with denticulate to slightly ciliate margins, dorsal leaves with long arista (as long as leaves) perpendicular to stems and branches in living plants, and axillary leaves triangular-ovate or broadly ovate. Molecular analyses based on ITS+5.8S and rbcL data also support it as a distinct species.